TINJAUAN HADITS TARBAWI SEBAGAI LANDASAN KEJUJURAN DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK : Kejujuran; Hadits Tarbawi; Pendidikan Karakter - Juliani, Siti; Huraerah, Siti; Safutra, Irwan; Muhammad Rendi Ramdhani (PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM, 2025)
The moral crisis and increasing acts of dishonesty in the learning environment demand the need to strengthen the character of honesty more effectively, especially through approaches based on Islamic values. This study aims to analyze and evaluate the function of tarbawi hadith as a basis in the formation of honesty character in students. The method used is a literature study by studying written sources and hadiths related to honesty and its application in Islamic education. The results showed that the tarbawi hadiths, especially those narrated by Abdullah bin Mas'ud and Abu Hurairah, provide a solid basis for instilling the value of honesty through habits, character assessment, and the formation of student integrity. The teachings of honesty contained in the hadith not only affect academic behavior, but also form a complete personality and good character. The conclusion of this study confirms that the integration of tarbawi hadith values in the curriculum and learning process is crucial to build the character of students who are honest and have integrity. The implication of this research is the importance of a systematic and sustainable character education strategy based on Islamic teachings to face moral challenges in the digital age.